The Effect of Vocabulary Self -Collection Strategy (VSS) On Student’ Vocabulary Mastery at SMPN 8 Kota Bengkulu - Julia Afriani (Teaching English and Language Learning English Journal, 2022)
The objective of this study is to know whether there is any significant effect of students who are taught by VSS (Vocabulary Self-Collection) strategy in student vocabulary mastery. The researcher used a quasi-experimental research. In this study, the researcher divided the subject of the study into two groups, an experimental group, and a control group. The sample in this study was students of VIII-4 consisted of 31 students as experiment class and VIII-5 consisted of 31 students as the control class. Therefore, total sample were 62 students. The finding showed that there was a significant effect of applying Vocabulary self-collection strategy (VSS) on the students’ vocabulary mastery at grade VIII of SMPN 8 Kota Bengkulu. In other words, the use of Vocabulary self-collection strategy (VSS) was generally effective to improve students’ vocabulary mastery at grade VIII of SMPN 8 Kota Bengkulu. Vocabulary Self Collection Strategy (VSS) is one of teaching strategy that can be considered to be implemented in teaching vocabulary in the English classroom especially in teaching reading text. So, it is expected for the teacher to encourage the students’ vocabulary mastery by implementing Vocabulary Self Collection Strategy. Keywords: Vocabulary Self -Collection Strategy (VSS), Vocabulary Mastery